MENGELOLA RISIKO PERUBAHAN IKLIM PADA AIR IRIGASI DI DAERAH KERING - Nurzanah, Wiwin; Pane, Yunita; Dewi, Irma (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Changes in temperature, precipitation, atmospheric carbon dioxide, or abnormal solar radiation are examples of climate changes that can affect irrigation water needs. Reduced river runoff and aquifer recharge in the Mediterranean basin are also likely to exacerbate water scarcity in existing arid environments This study aims to propose a systematic approach to identifying, analyzing, and responding to climate change risks to irrigation water in dry areas using the Risk Management process. The scope of this study is to use Monte Carlo simulation to manage climate change risks to irrigation water in dry areas. The first research method used is to make a list of identified climate change risks. Conduct qualitative and quantitative analysis of the identified risks and make responses to the identified risks. The results of the quantitative risk analysis indicate that crop production losses due to climate change are estimated at 69%, 57%, and 45% at 90%, 50%, and 10% confidence levels, respectively. The last phase of the risk management process is risk response. The proposed responses to climate change risks include strategies to avoid, transfer, mitigate, and/or accept these risks. This study has made three contributions. First, it adopts a well-known risk management methodology in climate change studies. Second, it measures the combined impact of climate change risks on irrigation water in dry areas. Third, it recommends a series of response strategies to help policymakers mitigate the adverse impacts of climate change on irrigation water.